The Mystery Of The Missing Necklace - Blyton, Enid (London Egmont, 2013)
There is a gang of thieves using Peterswood as their headquarters! Luckily, Fatty's disguises are better than ever - no one recognises him as a ballon seller or the old man in the village. He is just the person to get the Five Find-Outers to the bottom of this mystery .
Keywords: Children's Literature - Fiction : Detective / Mystery